The Educational Role of Teachers in Strengthening Students’ Digital Ethics Character at MI Irsyadul Islamiyah Bagan Batu - Ritonga, Sutan Oloan; Hafizon, Ahmad; Holiza, Siti (Journal of English Language and Education, 2026)
The rapid advancement of digital technology has significantly impacted students’ behavior, especially in their use of digital media in educational settings. Despite this, there is a gap in understanding the specific role of teachers in fostering ethical and responsible digital behavior. This study aims to explore the role of teachers in strengthening students’ digital ethics at MI Irsyadul Islamiyah Bagan, identifying implementation strategies and challenges. Using a descriptive qualitative approach, data were gathered through observations, interviews, and documentation. Findings reveal that teachers serve as educators, mentors, and role models, guiding students through values, exemplary behavior, positive habits, and effective communication with parents. However, challenges include varying digital readiness among students, exposure to inappropriate content, and the lack of comprehensive school policies. This study highlights the crucial role of teachers in ensuring students' digital competence and ethical behavior in the digital age.